An equivalent photovoltaic solar system to solve the problems of electricity in Iraqi houses - Abdulrahman Th. Mohammad; Amer Ibrahim Ismael (AIMS Energy, 2019)
Since 1991, Iraqi society suffers from the lack of electricity power because of an economic embargo imposed from 1991 to 2003 and the mismanagement that hit Iraq after its occupation in 2003. These reasons were leaded to major problems in the power plants and their transmission lines which led to insufficient power generation. To meet this problem, the Iraqi families were tended to use two types of generators (neighborhood and household generators) as alternative sources for compensating the lack of electricity. In this study, a 3 kW photovoltaic (PV) solar system was proposed to use the solar energy in Iraqi houses. An economic feasibility analysis by calculating the life cycle cost was investigated to compare the cost of PV system with the two alternatives sources of generators. At current market price of PV panels (700 IQD/W), a 3 kW PV system has the ability to supply the Iraqi house with electrical energy in total cost about (4,386,366 IQD ≈ 3655 USA$) for five years. The life cycle cost of PV system was investigated about 12.27% less than the two generators cost. Therefore, PV system is more economic in Iraqi houses under the deterioration in the electricity sector. Furthermore, the PV solar not pollutes the environment as the case of using generators.